Exploring factors that contribute to relationship building in a community center. (1st January 2019) - Colistra, Craig; Bixler, Robert; Schmalz, Dorothy
Abstract: Community centers are fundamental features of many communities as a space for social interaction and the development of social relationships, which can contribute to social capital, a sense of belonging, and a sense of community. An understanding of how relationships develop in community centers may help managers encourage relationship building and contribute to better individual and community health outcomes. A qualitative study was conducted at a public community center in the southeastern United States to understand how visitors' experiences of relationship building occur. In this case, relationships were facilitated by shared identities; support, reciprocity, and trust; and recurring programs. The results of this study can be considered by practitioners during program design to better embed social components in their programs that encourage relationship building.